Model Pembelajaran Berbasis Masalah Dalam Meningkatkan Aktivitas Dan Hasil Belajar Siswa Kelas VIII SMPN 14 Kota Bengkulu - Elvida Sari Yunilarosi; Jeri Stia Nanda (Kota Bengkulu, Provinsi Bengkulu, Indonesia, 2022)
Abstract: The purpose of this study was to describe teacher activities, student learning activities and student learning outcomes using problem-based learning in class VIII SMPN 14 Bengkulu. This type of research is classroom action research with descriptive method. The research consisted of two cycles, each cycle consisting of stages: action planning, action implementation, observation and reflection. The subjects in this study were teachers and all eighth grade students of SMPN 14 Bengkulu. The research instruments were tests, teacher observation sheets and student observation sheets. In cycle 1, the average teacher observation score was 29 (good criteria), and the average student observation score was 28 (good criteria). In cycle 2, the average teacher observation score increased to 31.5 (good criteria) and the average student observation score increased to 30 (good criteria). Learning outcomes in cycle 1 were analyzed based on the criteria of classical learning completeness and obtained an average value of 79.03 students and the percentage of classical learning mastery learning 72.22% with incomplete criteria. in cycle 2 the average increased to 90.83 with a percentage of completeness 91.67% with complete criteria. The results showed that the use of problem-based learning could increase teacher activity, student activity and student learning outcomes for class VIII SMPN 14 Bengkulu.Keywords: Problem Based Learning, Activities and Learning OutcomesAbstrak: Penelitian ini bertujuan untuk mendeskripsikan aktivitas mengajar guru dan aktivitas belajar siswa serta hasil belajar siswa dengan menggunakan model PBM di kelas VIII SMPN 14 Kota Bengkulu. Jenis penelitian ini adalah PTK dengan metode deskriptif. Penelitian ini terdiri dari 2 siklus, masing-masing siklus terdiri dari tahap: perencanaan tindakan, pelaksanaan tindakan, observasi dan refleksi. Subjek penelitian ini adalah guru dan seluruh siswa kelas VIII SMPN 14 Kota Bengkulu. Instrumen penelitian yang digunakan yaitu lembar tes dan lembar observasi, lembar observasi terdiri dari lembar observasi guru dan siswa. Pada siklus 1 rata-rata skor observasi guru adalah 29 (kriteria baik), sedangkan rata-rata skor observasi siswa adalah 28 (kriteria baik). Pada siklus 2 rata-rata skor observasi guru meningkat menjadi 31,5 (kriteria baik) dan rata-rata skor observasi siswa meningkat menjadi 30 (kriteria baik). Selanjutnya data hasil belajar pada siklus 1 dianalisis berdasarkan kriteria ketuntasan belajar klasikal dan diperoleh nilai rata-rata siswa 79,03 dengan persentase ketuntasan belajar klasikal belajar 72,22% dengan kriteria belum tuntas dan pada siklus 2 rata-rata meningkat menjadi 90,83 dengan persentase ketuntasan 91,67% dengan krteria tuntas. Hasil penelitian menunjukan bahwa penggunaan model PBM dapat meningkatkan aktivitas guru dan siswa serta hasil belajar siswa kelas VIII SMPN 14 kota Bengkulu.Kata kunci: Model Pembelajaran Berbasis Masalah, Aktivitas danÂ Hasil Belajar.